DETERMINAND IN THE MEDIATION OF CONSUMER STATISFACTION TOWARD CUSTOMER LOYALTY: DETERMINAND IN THE MEDIATION OF CONSUMER STATISFACTION TOWARD CUSTOMER LOYALTY - Ardiansyah, Haris (Jurnal Kompetitif Bisnis, 2021)
This research was aimed to determine the magnitude of the effect of brand image, product value, and reference group mediated by customer satisfaction on consumer loyalty of Satay H. Agus. This research appliedthe combine methods (Mixed Methods) by combining two forms of research approaches, namely quantitative and qualitative. In this research, qualitative was only to strengthen the results of the quantitative. The population in this study were consumers of Satay H. Agus. The sampling technique used accidental sampling with sample of 100 respondents and 8 interviews. The data were obtained from questionnaires using a likert scale and interviews. Analysis of the research data used path analysis. The results of the study explained that brand image, product value, group reference had a significant effect on customer satisfaction and product value, and customer satisfaction had a significant effect on customer loyalty. However, brand image and reference group do not have a significant effect on consumer loyalty. The product value factor is the biggest factor affecting consumer satisfaction in shaping consumer loyalty.